2019
DOI: 10.1021/acs.analchem.9b00965
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Regulated Boron Nitride Quantum Dots Electrochemiluminescence with Amplified Surface Plasmon Coupling Strategy for BRAF Gene Detection

Abstract: Because boron nitride quantum dots (BN QDs) have a wider gap (5.0–6.0 eV) than other QDs, the edge configurations, chemical functionalities, and heteroatom dopants can decrease and regulate the band gap of BN QDs, thereby ameliorating the QDs’ properties. Now, the precise control and regulation of BN QDs are still at an early stage and is a challenging task. Therefore, we used thiourea and l-cysteine as different sulfur precursors to regulate the BN QDs’ optoelectronic properties in this study. It is interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…A similar aqueous synthesis method of BNQDs was reported by others [71][72][73]. Later, Liu et al [74] used the microwave method to synthesize BNQDs with a QY 10.31% by dissolving boric acid and melamine in ultra-pure water and placing them in a microwave oven set at a frequency of 1000 Hz for 70 min at 120 o C. The authors also reported for the synthesis of sulfur S-regulated BNQDs using the same microwave method and same precursors (boric acid and melamine) [75]. They reported the use of thiourea and L-cysteine as the sulfur precursors, which yielded S-regulated BNQDs with different optoelectronic, electrochemiluminescence (ECL), and electro-optical properties.…”
Section: Hydrothermal Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…A similar aqueous synthesis method of BNQDs was reported by others [71][72][73]. Later, Liu et al [74] used the microwave method to synthesize BNQDs with a QY 10.31% by dissolving boric acid and melamine in ultra-pure water and placing them in a microwave oven set at a frequency of 1000 Hz for 70 min at 120 o C. The authors also reported for the synthesis of sulfur S-regulated BNQDs using the same microwave method and same precursors (boric acid and melamine) [75]. They reported the use of thiourea and L-cysteine as the sulfur precursors, which yielded S-regulated BNQDs with different optoelectronic, electrochemiluminescence (ECL), and electro-optical properties.…”
Section: Hydrothermal Methodsmentioning
confidence: 93%
“…As a result, the SPC-ECL effect suppressed the ECL-RET effect, thus enhancing the ECL signal (due to coupling of light emission with surface plasmon resonance) by about six times higher than BNQDs-Au NPs-hairpin DNA conjugates. The authors further reported on the use of S-regulated BNQDs along with AuNPs with higher ECL performance for BRAF gene detection and quantification using the same SPC-ECL strategy as discussed above [75]. Further, Liang et al [104] reported the first polarized-ECL biosensor developed using SPC-ECL strategy and fluorine-doped BNQDs to detect the K-ras gene.…”
Section: Electrochemiluminescence (Ecl) Responsesmentioning
confidence: 99%
“…[212] In recent years, a series of works have been done toward QD-based sensing of biomolecules, due to the novel PL, electrochemiluminescence (ECL) and electro-optical properties of QDs derived from layered materials. [59,63,157,[213][214][215][216][217] TMD QDs have been widely used to construct sensing platforms for biomolecules. Yan et al reported that Fe 3+ can quench the PL of WS 2 QDs through photoinduced electron transfer (Figure 12b).…”
Section: Biomolecule Detectionmentioning
confidence: 99%
“…A ratiometric and enzyme-free ECL sensing mode was constructed with the amplified surface plasmon-coupled ECL strategy. The proposed DNA sensor has a limit of detection of 0.3 pmol/L [56]. For these genetic studies, increased sensitivity may improve diagnosis.…”
Section: Circulating Biomarkersmentioning
confidence: 99%